Psychometric feasibility and dimensional profiling of the mental health continuum–short form in school-based physical education - Anas Anas; Dwi Lorry Juniarisca (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2026)
Background. Positive mental health is increasingly recognized as an educational resource in physical education; however, previous school-based studies often report mental health as a total score or a problem indicator and rarely show whether emotional, social, and psychological well-being form a useful profile for instructional decision-making. Objectives. This study evaluated the psychometric feasibility and dimensional profile of the Mental Health Continuum-Short Form (MHC-SF) in a senior high school physical education context. Method. A quantitative descriptive-psychometric design was applied using purposive school-based sampling. Instrument try-out involved 84 students, whereas the main profiling analysis involved 248 students from grades X and XI at Pamekasan 1 State Senior High School. Data were collected through a school-administered survey using the fourteen-item MHC-SF, which measures emotional, social, and psychological well-being. Analysis included item-total correlation, corrected item-total correlation, Cronbach’s alpha, Kaiser-Meyer-Olkin index, Bartlett’s test, exploratory eigenvalue inspection, descriptive statistics, and non-parametric group comparisons. Results. The instrument showed adequate feasibility: all items contributed positively, total-scale reliability was strong, and the item matrix was suitable for dimensional interpretation. Emotional well-being (M = 4.39 per item) and psychological well-being (M = 4.40 per item) were higher than social well-being (M = 3.48 per item). Significant but small differences appeared in social well-being by gender, psychological well-being by grade, and total and social well-being by age. Conclusion. The MHC-SF can support school-based positive mental health profiling, especially by identifying social well-being as a practical target for inclusive grouping, cooperative learning, peer support, and counselling coordination in physical education.